Phytochemical and Pharmacological Aspects of Murraya koenigii - Gupta, S.P.; Pande, M.S.; J. Ingale, Sanjay (Asian Journal of Chemistry, 2016)
An attempt has been made to provide upto date references that are categorized on the basis of phytochemical and pharmacological basis.